1998
DOI: 10.1017/s0950268898001216
|View full text |Cite
|
Sign up to set email alerts
|

The relationships of chronic hepatitis and cirrhosis to alcohol intake, hepatitis B and C, and delta virus infection: a case-control study in Albania

Abstract: The present study examined the effect of hepatitis B virus (HBV) and alcohol intake, and the role of hepatitis delta virus (HDV) and hepatitis C virus (HCV) in the aetiology of chronic liver disease in Albania. A total of 106 cases of liver cirrhosis or chronic hepatitis were compared to 195 control patients without these or other liver diseases. Adjusted odds ratios were 52.7 (95% CI 22.7-122) for HBV surface antigen, 26.9 (95% CI 4.9-147) for anti-HCV, 26.2 (95% CI 3-1-221) for anti-HDV, 2.4 (95% CI 1.3-4.4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
1
21
0
2
Order By: Relevance
“…Previous data have shown that Albania is a hyperendemic country for HBV infection and with an apparently low prevalence of HCV and HDV infection in patients with chronic liver disease and in different groups of general population [7][8][9]. Prior to the HBV vaccination, started as obligatory only for the new-borns, since 1995, the vertical transmission and the acquisition of infection in the childhood have been the main route of HBV transmission in Albania.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous data have shown that Albania is a hyperendemic country for HBV infection and with an apparently low prevalence of HCV and HDV infection in patients with chronic liver disease and in different groups of general population [7][8][9]. Prior to the HBV vaccination, started as obligatory only for the new-borns, since 1995, the vertical transmission and the acquisition of infection in the childhood have been the main route of HBV transmission in Albania.…”
Section: Discussionmentioning
confidence: 99%
“…Albania is a developing Mediterranean country where the prevalence of HBV infection is still high [7][8][9]. The vaccination program was started for newborns in 1995.…”
Section: Introductionmentioning
confidence: 99%
“…When the risk ratio is high (>10), as is the case for the risk factors and conditions under consideration here [16][17][18][19], the right-hand side of this expression approaches unity and the prevalence of the exposure among cases approximates the attributable fraction. Study-level prevalence data were adjusted to provide estimates of the fraction of cases attributable to infection with HBV or HCV as follows.…”
Section: Estimation Of Attributable Fractionsmentioning
confidence: 99%
“…Although not significant, interaction was suggested between HBsAg and alcohol intake (Kondili et al, 1998). A study among the Portuguese population also found that alcohol intake was the most important risk factor to HCC, with a frequency of 5.2% in patients with alcoholic hepatic cirrhosis (Oliveira et al, 2001).…”
Section: Introductionmentioning
confidence: 97%